INNERVATION OF BONES: WHY IT SHOULD NOT BE NEGLECTED? - Milovanović, Petar; Đurić, Marija (Medicinski podmladak, 2018)
Bones encompass a diverse network of sensory, sympathetic and even parasympathetic nerve fibers. While there is still insufficient understanding of the exact roles of these fibers in the skeleton, there is increasing evidence that they serve both afferent and efferent functions. Apart from pain transmission, some of their functions are regulation of bone remodeling, skeletal growth and fracture healing. That indicates that further research on bone innervation may shed more light on the main topics of bone biology, such as bone fragility in aged and osteoporotic individuals, alterations in fracture healing in various conditions, bone cancer pain, etc. This review article presents main morphological and functional characteristics of bone innervation.